Effects of Salinity on Soil Properties of Coastal Areas of (Babuganj, Bakerganj, Gournadi and Kalapara) in Bangladesh - Masum, Raja Md.; Naher, N.; Paul, A. K.; Alam, A. K. M. M. (International Journal of Bio-resource and Stress Management, 2017)
Bangladesh is highly vulnerable to sea level rise and salinity became a serious problem for agriculture all over the world. Soil salinity affects the parameters in soil and it is one of the major causes of decrease in the organic matter and nitrogen level in the southwestern part of Bangladesh. So, a field study was conducted to determine the effects of salinity on soil properties at Babuganj, Bakerganj, Gournadiupazilas of Barisal and Kalaparaupazilaof Patuakhali district of Bangladesh during the period of July to September 2016. Soil sampling was done by random sampling method at 0–50 cm and 50–100 cm depth. The dominant soil textural classes in the saline areas were silty clay. The soils pH of the surface horizon was slightly lower than those of the subsoil. Cation Exchange Capacity (CEC) of all these soils varied from 12.83 to 20.92 meq 100 g-1 soil. Electrical conductivity (EC) varied from 1.23 dS/m to 6.6 dS/m at Babuganj, Bakergnaj and Gournadi and moderately saline at Kalapara. The organic matter content was medium to high (0.62 to 1.6)% at Kalapara and Bakerganj but pretty low (0.39 to 1.03)% at Babuganj and Gournadi. Nutrient deficiencies for total nitrogen were quite dominant in the study areas. It was found that the clay content was the most fundamental property to control chemical properties of soils. From the correlation matrix it was found that organic matter showed significant negative relationship with CEC and Exchangeable Na, K, Ca and Mg showed mostly significant negative relationship with OM. Exchangeable sodium, potassium, calcium and magnesium were in high level and the dominant water soluble anions were Cl- and SO42-